2003
DOI: 10.1021/tx020105a
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on Protein Side Chain Modification by 4-Oxo-2-nonenal

Abstract: trans-4-Oxo-2-nonenal (ONE) has recently been demonstrated to be a direct product of lipid peroxidation. In earlier studies to elucidate the structure of the trans-4-hydroxy-2-nonenal (HNE)-derived fluorescent Lys-Lys cross-link, we showed that ONE was capable of both oxidative and nonoxidative cross-linking of amines. A more comprehensive study on nonoxidative modification of protein nucleophiles by ONE is described here, focusing on the initial Michael addition of imidazole, thiol, and amine groups to C2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
131
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 29 publications
(100 reference statements)
6
131
0
Order By: Relevance
“…Using the Lys derivative, they also have determined the relative yield of the various ONE adducts as a function of time and found that the ONL adduct was shown to survive at the expense of the short lived Schiff base and Michael adducts. Although the ONL represents the major long lived noncross-linked ONE modification on the Lys residues (23), previous studies of the ONE that missed this ONL adduct either mainly focused on the early and/or reversibly formed ONEderived adducts (11) or on adducts that could be readily detected in preparative isolation work by characteristic UVvisible spectral and NMR spectrometric signatures (21,41,42). In addition to ONE, 9,12-dioxo-10(E)-dodecaenoic acid, an ONE-like lipid peroxidation product that contains the carboxyl terminus, covalently reacts with the Lys residues to generate the same 4-ketoamide-type adduct (23).…”
Section: Lc-esi-ms/ms Analysis Of Onl-mentioning
confidence: 99%
“…Using the Lys derivative, they also have determined the relative yield of the various ONE adducts as a function of time and found that the ONL adduct was shown to survive at the expense of the short lived Schiff base and Michael adducts. Although the ONL represents the major long lived noncross-linked ONE modification on the Lys residues (23), previous studies of the ONE that missed this ONL adduct either mainly focused on the early and/or reversibly formed ONEderived adducts (11) or on adducts that could be readily detected in preparative isolation work by characteristic UVvisible spectral and NMR spectrometric signatures (21,41,42). In addition to ONE, 9,12-dioxo-10(E)-dodecaenoic acid, an ONE-like lipid peroxidation product that contains the carboxyl terminus, covalently reacts with the Lys residues to generate the same 4-ketoamide-type adduct (23).…”
Section: Lc-esi-ms/ms Analysis Of Onl-mentioning
confidence: 99%
“…Although 4-HNE has historically been the most well studied lipid peroxidation product (11), 4-ONE is also highly reactive (12). After forming Michael adducts, the aldehyde moiety may in some cases undergo Schiff base formation with amines of adjacent lysines, producing intra-and/or intermolecular cross-linked amino acids (13,14). In the case of 4-ONE, modification of lysine residues through 1,2-addition (Schiff base formation and the addition of water to the double bond) can also result in ketoamide adducts (15).…”
mentioning
confidence: 99%
“…18,23,[28][29][30][31] The addition by nucleobases also occurs at the C-1 position of ONE with the subsequent reaction at the C-2 position of the double bond to form 2-oxoheptyl-substituted etheno adducts. 19,[32][33][34][35][36] The acid-catalyzed reaction of -tocopherol with ONE in an acetonitrile solution proceeded by a different mechanism (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first step would be isomerization of the double bond of ONE from trans to cis, this being followed by the formation of the enol tautomer, 4-hydroxy-2,4-nonadienal. 23) Intramolecular nucleophilic addition between the 4-hydroxyl and 1-carbonyl groups of the enol molecule would then give a cyclic hemiacetal intermediate. If -tocopherol is present in the reaction mixture, the C-5 position of -tocopherol could attack the double bond at the C-5 A reaction mixture of -tocopherol (10 mM) and 2-(1-hydroxypentyl)furan (20 mM) in acetonitrile was incubated at 37 C for 3 h in the absence (A) or presence (B) of 50 mM HCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation